PERAN GURU DALAM INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM UNTUK PENCEGAHAN TIGA DOSA BESAR PENDIDIKAN DI SMP PELITA AL-QURAN MOJOTENGAH WONOSOBO - Aminah Al Zahra; Moh. Sakir; Firdaus Firdaus (CV. KAMPUS AKADEMIK PUBLISING, 2025)
A teacher spends the most time with students in the realm of education, they interact directly every day and provide learning that is not only theory but also practice in life. The objectives of this research are: To find out the efforts of teachers in integrating Islamic education values to prevent the three major sins of education; To find out the methods used by teachers in integrating Islamic education values to prevent the three major sins of education; To find out the challenges faced by teachers at Pelita Al-Quran Junior High School in the process of internalizing Islamic education values related to preventing the three major sins of education. The method used in this research is descriptive qualitative research method with the type of research is field research. Data collection techniques using observation, interview and documentation methods. The results showed that the teacher's efforts in integrating Islamic education values for the prevention of the three major sins of education there are several effective strategies implemented by the school, such as routine activities to study the book of Arbain Nawawi, the application of discipline, the formation of a team handling the three major sins of education. The methods applied by teachers in integrating Islamic education values are exemplary methods, habituation and advice. there are several challenges such as ineffective coordination between the cottage and the school, and the diversity of students' background.